Adaptação transcultural do instrumento “The Short Child Occupational Profile” (SCOPE) para a Língua Portuguesa do Brasil - Mazak, Mayara Soler Ramos (2021)
Background: The assessment The Short Child Occupational Profile (SCOPE) is a tool developed by American occupational therapists that makes it possible to systematically assess factors that facilitate or restrict participation in the occupations of children and adolescents, and these factors are based on the Model of Human Occupation (MOHO). In Brazil, there are some assessments created by occupational therapists who evaluate the children and adolescents population, however, despite the diversified nature of these assessments, the need for a change in the sense of evaluations is discussed, leaving the strict focus of the disabilities and assuming another configuration, more focused on the analysis of the client's skills and for the environmental variables that support occupational performance, contributing to better possibilities of production of life. In this sense, there is a need for further studies that develop or encourage the use of Occupational Therapy assessments that can assess the occupational participation of children and adolescents in the most different fields of activity of the profession, understanding SCOPE as an appropriate tool to this end. Objective: To carry out the cross-cultural adaptation of the SCOPE to the Portuguese language of Brazil. Method: The present study was developed based on the six steps of the method proposed by Beaton and collaborators (2000) regarding cross-cultural adaptation research, namely: Step 1. Initial translation of the assessment by two different translators; 2. Synthesis: the two translators, together, reached a single version of the assessment; 3. Back-translation: reverse translation done by three translators, the result of which was analyzed and validated by the main author of the original assessment; 4. Committee of Experts: the Portuguese version was analyzed by a committee composed of occupational therapists from different fields of activity who verified whether the translated version reflected the same content as the original version in relation to the equivalences: semantic, idiomatic, experiential and conceptual, and after adjustments, the pre-final version of the assessment was obtained; 5. Pre-Test: through an online interview, the pre-final version of the assessment was presented to 20 participants including family members of children and adolescents accompanied by occupational therapists in a school clinic to assess the understanding of the assessment's phrases ; 6. Final Review: the last step consisted of the analysis of the final report of the cross-cultural adaptation process by the author of the original assessment for the approval of the final version. Results: The translation and back-translation processes showed few discrepancies between the terms, obtaining good resolution between the translators for the elaboration of the synthesis. In relation to the Expert Committee, all suggestions for changes were analyzed and duly incorporated into the pre-final version of the assessment, which in turn, in the Pre-Test stage, presented a good or excellent understanding of the phrases by the participants. Finally, the Brazilian version of SCOPE was approved by the main author of the original. Conclusion: It was successful in the process of cross-cultural adaptation of the assessment for Brazil, currently entitled: Initial Occupational Profile of Children and Adolescents (SCOPE-BRASIL), being able to undergo further studies to obtain psychometric validation measures with the Brazilian population.